Do the undergraduate medical students perceive stress and what are the stressors? - John, Kevin A.; Naik, Poonam R. (International Journal Of Community Medicine And Public Health, 2020)
Background: Medical students have been reported to suffer from higher perceived stress compared to general population and students in the other academic fields. The objective of the study was to estimate the prevalence of stress and to identify the potential stressors among undergraduate medical students using perceived stress scale (PSS). Methods: A cross sectional study was conducted among 301 undergraduate medical students at a private medical college in Dakshina Kannada district, Karnataka. The extent of the stress was assessed using PSS-10 and a questionnaire was used to identify the potential academic, psychosocial and environmental stressors. Results: The mean PSS score was found to be 26.34±3 in this study. Moderate stress was observed in 68% of the study participants. The PSS score was higher among the 2nd year MBBS students. Stress was observed more among female medical students (74%). Inadequate study leave (92.4%), vastness of academic curriculum (84.1%), poor quality of food in mess or home (70.4%), accommodation away from home (60.1%) and high parental expectations (48.5%) were found to be the potential stressors in this study. Conclusions: The study results thereby highlight the need to plan tailored interventions to address the various stressors and prevent stress among the medical students.